Unwed Mothers in the Evangelical Lutheran Church in Tanzania - Mussa Kilengi (African Theological Journal for Church and Society, 2024)
This article examines the intersection of societal realities, religious convictions, and pastoral care within the Evangelical Lutheran Church in Tanzania (ELCT), focusing on unwed mothers. The article, rooted in John 8:1-11 which depicts Jesus’ encounter with the adulterous woman, aims to address the unique challenges faced by unwed mothers within the ELCT. It employs a multidisciplinary approach, including biblical exegesis, pastoral theology, and sociocultural analysis, to explore these complexities and highlight the compassionate aspects of Jesus’ response. The objectives are to examine societal and cultural influences impacting unwed mothers, analyse current pastoral practices within the ELCT, and propose a pastoral care framework that integrates biblical principles with cultural sensitivity. Ultimately, the article seeks to promote an inclusive and compassionate pastoral framework within the ELCT, enhancing the well-being of unwed mothers in the church community.